(untitled) (Journal of the College of Basic Education, 2024)
Objectives: This study aims to: Clarifying the semantic purposes of using singular, dual, and plural forms in place of each other. Detecting the co-occurrence of words in one case of forms. Knowing that some words are used in some forms but not in others. Different forms are frequently used without analogy in the Holy Qur’an. methods: The researcher followed the descriptive and analytical approach in his study. Results: The study found: Some words are used for the singular, dual, and plural. The use of some words is limited to one form and not another. Some words are in the singular form. The singular, dual, and plural forms exchange positions, as a matter of semantic expansion, and the plural forms are often used in place of the singular for glorification. Conclusion: The singular, dual, and plural forms exchange positions in the language of discourse as a matter of linguistic breadth, and linguistic use that contradicts analogy is considered one of the courage of Arabic, and the replacement of some forms varies, as some are used in forms rather than others, and some vocabulary requires the singular case, and others are used for the singular and plural.